Mobile game application framework with persuasive technology for learning English vocabulary among primary school students / Monther Mustafa Abubaker Elaish - Monther Mustafa, Abubaker Elaish (2019)
English is increasingly becoming an essential second language as well as a language for communication. M-learning is receiving global attention especially among English language learners. Non-native English students like Arabic students face difficulties in such a way that they lack motivation which leads to poor performance in learning English vocabulary. However, if they are persuaded, it may improve their performance. Therefore, persuasive technology is important in improving user motivation and engagement. It is designed to change the behaviours or attitudes of the users. However, unlike many other fields of endeavour, it is difficult to find any application that uses persuasive technology in the field of mobile game-based English learning. Thus, this research aims to develop a mobile game framework based on persuasive guideline with the purpose to enhance motivation and performance of Arabic students in learning English vocabulary. This study proposes a mobile game framework using a specific guideline extracted from persuasive principles. Design Science Research Method has been used for this research which includes identification of the problems and motivation such as the definition of the objectives of a solution, the design and development, the demonstration, the evaluation, and communication. The proposed framework comprised a guideline developed and validated by experts in the domains of education, gaming, and software development. While, the mobile game application was developed based on the proposed framework and evaluated by primary school’s students selected from International Modern Arabic School, Putrajaya, Malaysia. Experimental method was used to measure the performance and motivation. The results showed that there is an increase in the experimental group performance. Additionally, the experimental group showed significant increase in terms of motivation when the time factor was included. This study concluded that mobile game framework with persuasive guideline can improve Arabic students’ motivation and performance in learning English language. This framework can assist practitioners and developers in designing mobile game application for learning English vocabulary. Moreover, students can use the application to improve their English language skills. This research also contributes to the literature of persuasive technology by incorporating its concept into theory of game-based English learning that form the bases for further research.